Mapping cultural ecosystem services in the hyper arid environment of south of Jordan - Albalawneh, Abeer; Al-Assaf, Amani; Sweity, Amer; Hammour, Wafa’a Abu; Kloub, Khawla; Hjazin, Amgad; Kabariti, Rabab; Abu Nowar, Lana; Tadros, Maher J.; Aljaafreh, Safaa; Diab, Mai; Alwidyan, Jafar; et al. (Frontiers in Environmental Science, 2022)
Cultural ecosystem services (CESs) refer to the non-monetary benefits that nature provides humans. This study aimed to allocate and map the CESs in the hyper arid region at the southern part of Wadi Araba as a unique ecosystem in Jordan. 296 residents were individually interviewed using a structured questionnaire. The respondents were prompted to indicate CES by drawing dots on a geo-referenced landscape map corresponding to any areas they considered as CES. The results were mapped and subjected to hot-spot and statistical analyses using a geographical information system (GIS)-based spatial evaluation and statistical analysis using the kernel density estimation (KDE) and Getis-Ord Gi* statistics with inverse distance weighted (IDW) interpolation. Overall, the CESs provided by their region were appreciated by most residents. The hot-spot analysis revealed that those core hot-spots (Getis-Ord-Gi* values equal to p = 0.01) covered 19.6% while core cold spots covered 21.2% of the study area. The respondents expressed eagerness to contribute to a constant flow of CESs if the restoration plans are fully supported by the local community. The CES maps generated using the data collected in the present study can serve as baseline measures of the CES provisions subject to change based on the parameters of each development scenario. Furthermore, these maps could help support current and future management efforts by integrating communities’ preferences into development and conservation initiatives, thereby ensuring more efficient and effective utilization of CESs.